Media coverage of Chinese investment in the United States: Politics and missed opportunities. (June 2021) - Wells, Rob; Zeng, Ka; Wilkins, Austin
This article explores how five leading U.S. publications covered Chinese direct investment in the United States from 2000 through 2019. The authors find a lack of in-depth coverage of Chinese companies that were significant investors in the United States even though the news organizations offered fairly comprehensive coverage of the broad strokes of U.S.–China relations. The coverage shortfall comes despite Chinese foreign direct investment rising from US385 million to more than US40 billion a year during the study period. An analysis of leading news narratives and sentiment finds a dramatic rise in negative news sentiment during the Trump administration's trade war with China from 2017 to 2019.